In Situ Measurement of Seeking Speed and Seeking Induced Head-Disk Interface Instability in Hard Disk Drives - Yu Wang; Xiongfei Wei; Yanyang Zi; Kwok-Leung Tsui (Shock and Vibration)
This paper investigated the instability of head-disk interface caused by the voice coil motor (VCM) end crashing the crash stop during the seeking of magnetic head. To make the whole process of that clear, an in situ measurement method based on maximum likelihood estimation and extended Kalman filter for seeking speed at component level was developed first and was then calibrated by a high speed camera. Given a crash between VCM end and crash stop that may be a consequence of the continuous increasing seeking speed, the seeking speed was carefully controlled by using our developed method to find a critical value that may induce vigorous head-disk interface instability. Acoustic emission sensor and laser Doppler vibrometer were used to capture the transient dynamic behaviors of magnetic head when the crash is happening. Damage analysis and mode identification were carried out to reveal the relationship between the damage patterns on disk surface and head dynamics. The results of this study are helpful to optimize the track seeking profile during the HDD operation, as well as the design of components such as head and head arm.